Simply. ( x − 3 z 7 ) ( 2 x 3 y z −...

enmobladatn

enmobladatn

Answered

2022-07-28

Simply.
( x 3 z 7 ) ( 2 x 3 y z 1 ) 3

Answer & Explanation

Tristan Pittman

Tristan Pittman

Expert

2022-07-29Added 14 answers

Solution:
( x 3 z 7 ) ( 2 x 3 y z 1 ) 3 = ( 1 x 3 z 7 ) ( z 1 2 x 3 y ) 3 = ( z 7 x 3 ) ( z 3 ( 2 x 3 y ) 3 ) = ( z 7 x 3 ) ( 1 8 x 9 y 3 z 3 ) = z 7 8 x 12 y 3 z 3 = z 4 8 x 12 y 3

Do you have a similar question?

Recalculate according to your conditions!

Ask your question.
Get your answer.

Let our experts help you. Answer in as fast as 15 minutes.

Didn't find what you were looking for?